Low temperature microhardness of Xe-intercalated fullerite C₆₀ - Fomenko, L.S.; Lubenets, S.V.; Natsik, V.D.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B. (Физика низких температур, 2005)
The Vickers microhardness of Xe-intercalated polycrystalline fullerite C₆₀ (XexC₆₀, x ≃ 0.35) is measured in a moderately low temperature range of 77 to 300 K. A high increase in the microhardness of the material (by a factor of 2 to 3) as compared to that of pure C₆₀ single crystals is observed. It is shown that the step-like anomaly in the temperature dependences of the microhardness of pure C₆₀ single crystals recorded under the orientational fcc-sc phase transition (Tc ≃ 260 K) is also qualitatively retained for XexC₆₀, but its onset is shifted by 40 K towards lower temperatures and the step becomes less distinct and more smeared. This behavior of ̅NV(T) correlates with x-ray diffraction data, the analysis of which revealed a considerable influence of xenon interstitial atoms on the peculiar features of fullerite thermal expansion due to orientational phase transitions (see the paper by A.I. Prokhvatilov et al. in this issue).